Pseudoexfoliation syndrom – etiopatogenesis and clinical course - Ludwisiak-Kocerba, Lidia; Hevelke, Agata; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Pseudoexfoliation syndrome is an ocular manifestation of a systemic elastosis. Exact etiology of this condition remains unknown. The basic pathogenetic concept of PEX is a pathological process of the extracellular matrix, characterized by the excessive production of an abnormal extracellular material which aggregates and accumulates and is not degraded in vivo. This material is produced primarily by the non pigmented epithelium of the ciliary body, the posterior iris pigment epithelium, and the preequatorial lens epithelium, while the corneal endothelium, trabecular cells, and vascular endothelia and smooth muscle cells of the iris have also been implicated. PEX material has a complex glycoprotein/proteoglycan, composition containing glycosaminoglycans (heparan sulfate, chondroitin sulfate, dermatan sulfate, hyaluronic acid). The prevailing presence of elastic fiber epitopes, mainly elastic microfibrillar components (elastin, vitronectin, amyloid P, fibrillin-1, LTBP-1), has led to the current theory explaining PEX as a type of elastosis, affecting especially elastic microfibrils. Ocular deposition of pseudoexfoliation material can lead to many complications in intraocular surgery like increased risk of zonular dehiscence, capsular rupture, vitreous loss during cataract extraction. Special attention is required before, during and after surgery.